7
$\begingroup$

Wolfram's website lists this as a limit representation of the natural log:

$$\ln{z} = \lim_{\omega \to \infty} \omega(z^{1/\omega} - 1)$$

Is there a quick proof of this? Thanks

$\endgroup$
1
  • 2
    $\begingroup$ It is quite interesting that this should come up just now. I used this very limit in this answer last night. $\endgroup$
    – robjohn
    Jan 20, 2013 at 1:24

4 Answers 4

10
$\begingroup$

$\ln z$ is the derivative of $t\mapsto z^t$ at $t=0$, so $$\ln z = \lim_{h\to 0}\frac{ z^h-1}h=\lim_{\omega\to \infty} \omega(z^{1/\omega}-1).$$

$\endgroup$
8
$\begingroup$

You have $z^{1/\omega}= \exp ( \ln(z)/\omega)= 1+ \ln(z)/\omega + o(1/\omega)$, so $\ln(z)=\lim\limits_{\omega \to + \infty} \omega (z^{1/\omega}-1)$.

$\endgroup$
1
  • $\begingroup$ Yes, of course...as long as a definite branch of the complex logarithm is implicitly chosen and used. In this case it seems to be the "usual" branch which is used ("erase" the non-positive real axis, taking zero as the argument of the whole positive real axis). Otherwise the first equality can easily be false. $\endgroup$
    – DonAntonio
    Jan 20, 2013 at 2:46
3
$\begingroup$

Another way is to use L'Hôpital's rule. Write $w(z^{1/w}-1)$ as $$\frac{z^{1/w}-1}{1/w}\,.$$ Note that both the numerator and the denominator go to 0 as $w\to\infty$; thus, we can apply L'Hôpital's rule: $$\lim_{w\to\infty}\frac{z^{1/w}-1}{1/w} =\lim_{w\to\infty}\frac{\frac{d}{dw}(z^{1/w}-1)}{\frac{d}{dw}1/w}=\lim_{w\to\infty}\frac{(-1/w^{2})(\ln z)z^{1/w}}{-1/w^2}=\ln z \,. $$ In the numerator, we used $z^{1/w}=e^{(1/w)\ln z}$ and then proceeded as follows: $$ \frac{d}{dw}e^{(1/w)\ln z}=\left[\frac{d}{dw}\Big((1/w)\ln z\Big)\right]e^{(1/w)\ln z}=\left[(-1/w^{2})\ln z\right]z^{1/w}\,. $$

$\endgroup$
0
$\begingroup$

Not a formal proof, only a bit of intuition. Substituting $x=\ln(z)$ (therefore $z=\exp(x)$), and $n$ instead of $\omega$, this limit is aligned with the infamous Euler's limit for the exponential.

$$ x = \lim_{n \to \infty} n (\exp(x) ^{1/n} - 1) = \lim_{n \to \infty} n (\exp(x/n) - 1 $$

We put the limit aside, and use some trivial algebraic manipulations. Then we put the limit back, to get Euler's limit:

$$\exp(x) = \lim_{n \to \infty} \left( 1 + \frac{x}{n} \right)^n$$

$\endgroup$
0

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .